Performance Prediction and Parametric Analysis of Small Diameter Heat Exchangers Based on Distributed Parameter Model - Li Jinbo; Zhao Fufeng; Li Rixin; Du Shunkai; Zhi Changshuang; Liu Yingwen (Zhileng xuebao)
Based on a three-dimensional distributed parameter model, a simulation model of a small-diameter heat exchanger in the indoor unit of a split-household air-conditioner was established, and the performance metrics were computed, including the total heat load, sensible heat load, latent heat load, refrigerant-side pressure drop, and air-side pressure drop. The effects of the tube length, refrigerant mass flow rate, air volumetric flow rate, air inlet temperature, and air inlet relative humidity on the heat exchanger performance metrics were determined under different working conditions. For the 5 mm diameter heat exchanger considered in this study, the corresponding tube length range was 0.6~0.7 m, achieving good heat transfer with a small pressure drop. Owing to the comprehensive influence of the heat transfer coefficient and the effective mass transfer time, when the volumetric flow of air was in the range of 600–700 m3/h, the latent heat load reached a maximum of 426 W. With an increase in the air inlet temperature, the sensible heat load first increased and then decreased.